Development of Independent Curriculum Printable Modules Pancasila Education Subject Class V SD Nurul Islam Cileungsi - Rio Ardi; Nurdin Ibrahim; Dedi Supriadi (CV Media Inti Teknologi, 2024)
This study aims to develop learning media in the form of printed modules for the Merdeka Curriculum in the fifth grade Pancasila Education subject at SD Nurul Islam, Bogor Regency. This research uses a combination of the Borg and Gall development model with Rowntree which results in a development model with the following steps; preliminary study, planning, writing preparation, initial draft development, initial trial, revision of trial results, main product field test, product revision, wide-scale field trial, final product revision and module dissemination and implementation. The feasibility test uses the validation of material experts, media experts and instructional design experts and considers the results of the user test of students and teachers. The material experts' feasibility test yielded results of 91%, the media design experts' 90%, the instructional design experts' 87%, the student users' 94%, and the instructor users' 94%. received the designation of